Hubungan Supervisi Kepala Ruangan dengan Penerapan SOP Pencegahan Risiko Jatuh - Aulya Wahyu Ismayanti; Dyah Wiji Puspita Sari; Retno Issroviatiningrum (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Supervision is part of the directing function carried out by supervisors to improve nurse performance. Falls result in injuries such as broken bones or bleeding and can cause death. This is because nurses' lack of optimal compliance with the implementation of fall risk prevention SOP can increase the incidence of patients falling while being treated. One of the incidents of falls comes from not yet optimal SOP planning in an institution. The purpose of this research is to analyze the relationship between head of room supervision and the implementation of fall risk prevention SOP at the Sultan Agung Islamic Hospital.This research is a quantitative research with a cross-sectional approach. Data collection was carried out using questionnaires and observation sheets. The research sample consisted of 50 respondents. This research uses a total sampling technique and is processed statistically with the correlation test used in this research is the spearman rank test.The results of the spearman rank test on the room head supervision data with the implementation of fall risk prevention SOP obtained a p value of 0.000 (<0.05). For further research, it is recommended to expand the scope of research by involving more respondents and hospital institutions in order to obtain more generalizable results.